Alat Pendeteksi Asap Rokok dengan Peringatan Suara Menggunakan Sensor Mq-2 dan Mq-135 - Haniza, Haniza; Pamungkas, Berlian; Saputra, Zanu; Novitasari, Novitasari (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Polman Babel is one of the places for the nation's next generation to carry out the teaching and learning process in Bangka Regency to respond positively to regulations related to the No Smoking Area (KTR). This is realized by the presence of warning boards regarding the prohibition of smoking at several locations. The smoke-free area policy has been enforced, but there are still some violators and lack of awareness to comply with the regulation. To overcome this problem, a smoke detector is needed that can be used in the campus environment. A cigarette smoke detector using MQ-135 sensor and MQ-2 sensor that can emit a sound to encourage smokers to put out their cigarettes and leave the area. Detection testing was carried out with various sensor distances from the source measured from 50 cm to 200 cm with the appearance of warnings from loudspeakers. The farther the sensor is from the smoke source, the smaller the detection value will be, depending on the position of the sensor and the smoke source.